Development of Pavement Maintenance Management System (PMMS) for Urban Roads - Chopra, Tanuj (My University, 2018)
Roads are the fundamental infrastructure requirement for the development of a nation, contributing to the National economy. The availability of good and serviceable roads is as important in an urban area as other services like water supply, electricity, drainage, telecommunication etc. Any shortfall in the serviceability of urban roads immediately results into great dissatisfaction among the commuter and the urban population. Regular Maintenance of these city roads is very much essential and should not be neglected, particularly in developing countries like India. The magnitude of work involved in maintaining the road networks to required serviceability is very large but the budget available for the maintenance is generally not enough to meet the requirements. Most of the maintenance and rehabilitation treatments provided on the urban roads is based upon the experience or judgment of the department engineers only. Therefore, there is a need of develop an effective scientific methodology and programs for deciding the optimum maintenance and rehabilitation strategies for the city road networks. Development of an effective Pavement Maintenance Management System (PMMS) would provide various project and programme level analysis and will also help to calculate the remaining service life of pavements & to prioritize the urban road sections based upon the available maintenance funds. Rawat (1998) & Shah (2016) stated that the urban roads in India have different types of problems as compared to other categories of road such as higher repetitions of traffic with problem of overloading, encroachment on the road side area, lack of proper drainage system which may lead various distresses in pavements, and various utility services which necessitate frequent digging thereby disturbing homogeneity of pavement structure. Therefore, there is a urgent need to develop a Pavement Maintenance Management System (PMMS) for the urban road networks, as it constitutes around 9% of total road network length in India, which would be useful to the city agencies such as Municipal Corporations, Public Works Department & other agencies involved in planning & executing pavement maintenance strategies in a scientific manner under both the options of constrained & unconstrained budget. The proposed PMMS methodology includes: identification and selection of the urban road network, collection of field data and database management, and calibration and validation of HDM-4 pavement deterioration models for local conditions. The procedures and equipments used for collection of various kinds of field data on sixteen pavement sections have been described. The data for vehicle fleet plying on the road network, maintenance and rehabilitation activities, cost data for various types of M&R works, and the road user cost data, as obtained from field and relevant government publications has been presented. The time series pavement distress data of cracking, ravelling, potholes, rutting and roughness have been collected for the year 2012, 2013, 2014 and 2015. The HDM-4 road deterioration models have been calibrated for the selected urban road sections under local conditions using the time series pavement distress data collected for the year 2012, 2013, 2014 and 2015. The calibrated HDM-4 pavement deterioration models, considered in this study have been validated by comparing the values of distresses predicted in year 2014 & 2015 by the HDM-4 model with those observed in the field in year 2014 & 2015 , for all the road sections of urban network. The difference between the observed and predicted distress values is not statistically significant at 5% level of significance. Therefore, the calibrated deterioration models have been used for time series prediction of distresses on all pavement sections. In the present study, different aspects of project and network level PMMS have been studied using various modules of HDM-4. The project level analysis included determination of optimum maintenance & rehabilitation, comparison of scheduled and condition responsive maintenance strategy and estimating remaining service life of urban road sections. The optimum maintenance strategies have been determined based on highest NPV/Cost ratio. The network analysis included life cycle-cost analysis of urban road network giving an unconstrained budget works programme, optimization of resource allocation for maintenance giving constrained works programme and prioritization of urban road sections for maintenance on the basis of decreasing NPV/Cost ratio. The two emerging soft computing techniques; neural network and GP have also been applied on the data set of 16 road sections of Patiala City for the prediction of pavement distress. Four models (i.e., Model1, Model2, Model3 and Model4 for Cracking Progression (CA), Ravelling Progression (RA), Potholes Progression (POT) and Roughness Progression (IRI), respectively) have been developed for the prediction pavement distress. In the present study, all the developed models have the value of R2 > 80%. Neural network and GP models have been developed and compared with the help of fitness functions i.e., Coefficient of Determination (R2) and Root Mean Square Error (RMSE). It has been observed that GP models provide the value of R2 is higher and RMSE is less as compared to neural network, when applied on validation data sets. The next objective of the present study is to reveal the role of the Geographical Information System (GIS) technology in the enhancement of urban PMMS. A variety of spatially integrated data are important to pavement management decision making. Thus, the thesis presents a scientific approach for the development of pavement maintenance management system for the urban road networks. The suggested approach could be adopted for development of PMMS for other cities in India and for other categories of roads such as National Highways, State Highways, Major District Roads & Village Roads by using the inputs of PMMS methodology used in this study. This study would be very beneficial to the various government local agencies of Patiala city in defining & developing road maintenance strategies & work standards for maintenance in a systematic & scientific manner and to ensure the proper utilization of the available maintenance budgets by optimising the investment decisions based upon certain economic indicators such as NPV/cost ratio.
PMMS study for Patiala city using HDM-4 and Genetic Programming
Keywords: PMMS; Urban roads; Genetic Programming; HDM-4; GIS